2006
DOI: 10.1089/jwh.2006.15.202
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Daily Steps and Body Composition in Postmenopausal Women

Abstract: We demonstrated that postmenopausal women who take more daily steps have more favorable adiposity profiles. Additionally, the average body mass index (BMI) of the women in the active category (accumulating an average of 10,023 +/- 240 steps per day) was in the recommended range (24.1 +/- 0.9 kg/m(2)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 40 publications
5
51
0
Order By: Relevance
“…To our knowledge, this observation is consistent with all recent investigations (TudorLocke et al, 2001;Chan et al, 2003;Thompson et al, 2004;Hornbucle et al, 2005;Wyatt et al, 2005;Krumm et al, 2006;Dwyer et al, 2007;Clemes et al, 2007). On the other hand, this relationship is complicated in cross-sectional data using a self-reported questionnaire because of methodological problems (Erlichman et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this observation is consistent with all recent investigations (TudorLocke et al, 2001;Chan et al, 2003;Thompson et al, 2004;Hornbucle et al, 2005;Wyatt et al, 2005;Krumm et al, 2006;Dwyer et al, 2007;Clemes et al, 2007). On the other hand, this relationship is complicated in cross-sectional data using a self-reported questionnaire because of methodological problems (Erlichman et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…The sensitivity and reliability are well examined, and some brands are comparable to more expensive accelerometers (Tudor-Locke et al, 2002;Schneider et al, 2003). Recently, many cross-sectional studies observed that body mass index (BMI) and percentage of body fat (%BF) were inversely associated with pedometer-determined physical activities (Tudor-Locke et al, 2001;Chan et al, 2003;Thompson et al, 2004;Hornbucle et al, 2005;Krumm et al, 2006). The correlation coefficients between steps/day and BMI or %BF reported in these studies were from Ϫ0.30 (TudorLocke et al, 2001) to Ϫ0.479 (Hornbucle et al, 2005) and from Ϫ0.27 (Tudor-Locke et al, 2001) to Ϫ0.713 (Thompson et al, 2004), respectively, and those who accumulate more ambulatory activity have significantly lower BMI values, %BF, and waist circumferences.…”
Section: Introductionmentioning
confidence: 99%
“…By using pedometer-derived measures of physical activity, researchers were able categorize people by activity level and detect associations with important physiological measures associated with chronic disease in middle-aged to older women. These results were in line with those found in a similar study by Krumm, Dessieux, Andrews, and Thompson (2006), who successfully used the SW-200…”
Section: Objective Measuressupporting
confidence: 92%
“…[23] Based on research to report individuals who take >9,000 steps per day are more likely to be classified as normal weight, [11,24,25] recommendations for health have recently evolved to include steps per day. [26] Despite averaging >10,000 steps per day, males in the current investigation are classified as being overweight based on its mean BMI and as having above average body fat.…”
Section: Discussionmentioning
confidence: 99%
“…BMI, percent body fat, waist circumference, hip circumference) have been reported in samples of older males and females. [1,11,13,25] In the college-aged population, research has reported significant inverse associations between certain indices of physical activity (steps·day ) and BMI and body fat percent in females; [10,17] however, the association was only significant for males when season was considered. [10] While accumulating a certain number of steps per day has been integrated into the cardiovascular exercise recommendations for health, results from the current study suggest its association with body composition is population-specific and may not necessarily confer a healthy body weight or composition.…”
Section: Discussionmentioning
confidence: 99%